Reflections on Sustainable Consumption in the Context of COVID-19 - Perkins, Krystal M.; Velazquez, Luis; Munguia, Nora (Frontiers in Sustainability, 2021)
The COVID-19 pandemic has abruptly disrupted progress toward many of the Sustainable Development Goals (SDG). The UN has stressed the imperious need to design short-term responses to halt and reverse the adverse effects of the current COVID-19 crisis. Researchers have also scrutinized the feasibility and potential counterproductivity of the SDGs in our post-pandemic world. This perspective paper holds a more hopeful outlook and believes that the COVID-19 pandemic has the potential to prompt efforts to carry out the UN’s 2030 Agenda. This paper engages the theme of “sustainable consumption” in the context of our COVD-19 world. We discuss two perspectives or bodies of work-supply chain sustainability and post-colonial theory to frame our thinking about sustainable consumption. Each of these perspectives alerts us to the possibilities of the SDGs and the gaps in the inherent orthodoxy of sustainable consumption approaches and practices. We hope these observations provoke more questions and avenues for future research.